Implementation of the Health Law in Providing Legal Protection for Medical Personnel and Patients in Indonesia - Fenti Maya Sari; Imam Ropii (Rechtsvinding, 2026)
This study aims to analyze the regulation, implementation, and effectiveness of Law Number 17 of 2023 concerning Health in protecting medical personnel and patients from medical disputes, using a normative legal approach method through a literature study of primary materials in the form of related and secondary laws such as journals and health law doctrines, followed by qualitative analysis based on legal reasoning to interpret norms, consistency of regulations, and juridical implications in service practice. The law regulates balanced protection through the rights of medical personnel to a legal umbrella while complying with professional and patient standards for complete information and informed consent, its implementation is realized through hospital mediation, Professional Disciplinary Councils, and safety protocols that reduce malpractice and violence, while its effectiveness can be seen from reducing litigation conflicts, improving service quality, and public trust through socialization and audits of the Ministry of Health which ensures a harmonious health ecosystem in Indonesia.